A correlative approach, combining chlorophyll a fluorescence, reflectance, and Raman spectroscopy, for monitoring hydration induced changes in Antarctic lichen Dermatocarpon polyphyllizum - Mishra, Kumud Bandhu; Vítek, Petr; Barták, Miloš (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2019)
Lichens are successful colonizers in extreme environments worldwide, and they are considered to have played an important role during the evolution of life. Here, we have used a correlative approach, combining three optical signals (chlorophyll a fluorescence (ChlF), reflectance, and Raman spectra), to monitor hydration induced changes in photosynthetic properties of an Antarctic chlorolichen Dermatocarpon polyphyllizum. We measured these three signals from this lichen at different stages (after 4 h, 24 h, and 48 h) of hydration, and compared the data obtained from this lichen in "dry state" as well as in different "hydrated state". We found that dry state of this lichen has: (1) no variable ChlF, (2) high reflectance, with no red-edge and almost zero photochemical reflectance index (PRI), and (3) low-intensity Raman bands of their carotenoids. Furthermore, 4 h of hydration, increased its relative water content (RWC) by 93%, showed red-edge in reflectance spectra, and changed the maximum quantum yield of PSII photochemistry (Fv/Fm) from 0 to 0.57 ± 0.01. We found that reflectance indices, normalized difference index (NDVI) and PRI, significantly differed between brown and black/green surface areas, at all hydration stages; whereas, a shift in the Raman ν1(CC) band, between brown and black/green surface areas, occurred in 24 h or 48 h hydrated samples. These data indicate that hydration shortly (within 4 h) activated functions of photosynthetic apparatus, and the de novo synthesis of carotenoids occured in 24 h or 48 h. Furthermore, exposure to high irradiance (2000 μmol photons m-2 s-1), in 48 h hydrated lichen, significantly reduced Fv/Fm (signifies photoinhibition) and increased PRI (represents changes in xanthophyll pigments). We conclude that the implication of such a correlative approach is highly useful for understanding survival and protective mechanisms on extremophile photosynthetic organisms.
Keywords: fotosyntéza; Raman mapping; Spectrum Analysis, Raman; Chlorophyll A; voda; Chlorophyll a fluorescence transient; Ramanova spektroskopie; Optical signal; Extremophile organisms; lišejníky; počítačové zpracování signálu; fluorescence; Lichens; Photosynthesis; Carotenoids; Signal Processing, Computer-Assisted; chlorofyl a; Fluorescence; Reflectance spectra; Water